Free Fatty Acid (FFA) and Hydroxy Carboxylic Acid (HCA) Receptors - Stefan Offermanns (2013)
Saturated and unsaturated free fatty acids (FFAs), as well as hydroxy carboxylic acids (HCAs) such as lactate and ketone bodies, are carriers of metabolic energy, precursors of biological mediators, and components of biological structures. However, they are also able to exert cellular effects through G protein–coupled receptors named FFA1–FFA4 and HCA1–HCA3. Work during the past decade has shown that these receptors are widely expressed in the human body and regulate the metabolic, endocrine, immune and other systems to maintain homeostasis under changing dietary conditions. The development of genetic mouse models and the generation of synthetic ligands of individual FFA and HCA receptors have been instrumental in identifying cellular and biological functions of these receptors. These studies have produced strong evidence that several FFA and HCA receptors can be targets for the prevention and treatment of various diseases, including type 2 diabetes mellitus, obesity, and inflammation.